Vernalization and the chilling requirement to exit bud dormancy: shared or separate regulation? - Brunner, Amy M.; Evans, Luke M.; Hsu, Chuan-Yu; Sheng, Xiaoyan (Frontiers in Plant Science, 2014)
Similarities have long been recognized between vernalization, the prolonged exposure to cold temperatures that promotes the floral transition in many plants, and the chilling requirement to release bud dormancy in woody plants of temperate climates. In both cases the extended chilling period occurring during winter is used to coordinate developmental events to the appropriate seasonal time. However, whether or not these processes share common regulatory components and molecular mechanisms remain largely unknown. Both gene function and association genetics studies in Populus are beginning to answer this question. In Populus, studies have revealed that orthologs of the antagonistic flowering time genes FT and CEN/TFL1 might have central roles in both processes. We review Populus seasonal shoot development related to dormancy release and the floral transition and evidence for FT/TFL1-mediated regulation of these processes to consider the question of regulatory overlap. In addition, we discuss the potential for and challenges to integrating functional and population genomics studies to uncover the regulatory mechanisms underpinning these processes in woody plant systems.